Execution of Death Penalty Verdict Who Already Have Permanent Legal Force in Drug Cases - Daru Sukma Syahrul Ramadhan (Zona Law And Public Administration Indonesia, 2023)
Drug crime has a broad impact on the lives of the community, the nation and the State, so that this crime if not anticipated will damage the order of life of the community, the nation. Indonesia as a State of Law is very consequential to eradicate these crimes by issuing Law Number 222 of 19977 concerning Drugs, and Law Number 5TTahun1997 concerning Psychotropic Substances with the threat of maximum criminal penalties observed and fined The problem of adult crime in Indonesia is a hot topic of discussion, considering that some people are pro and contra about international law and national law, namely: Human Rights Declaration, Covenant Civil and Political Rights, United Nations General Assembly Resolution 2200a (XXI), the 1945 Constitution, Law No. 39 of 1999, and Law No. 5 of 1998. Meanwhile, for the group of people who continue to defend the death penalty, based on the thought, that the death penalty is still applied in Indonesia, considering that the developing Indonesian nation still needs the crime to provide lessons for the community not to commit death crimes which is applied in Indonesia Community groups who are anti-death penalty express their thoughts, That the death penalty is contrary to those threatened with the death penalty. Moreover, it is related to drug cases whose impact is so very broad on the joints of life of the nation, and the nation, especially for the younger generation who are expected to become the next generation of the nation